2015
DOI: 10.1109/tvcg.2015.2413786
|View full text |Cite
|
Sign up to set email alerts
|

Learning Visualizations by Analogy: Promoting Visual Literacy through Visualization Morphing

Abstract: We propose the concept of teaching (and learning) unfamiliar visualizations by analogy, that is, demonstrating an unfamiliar visualization method by linking it to another more familiar one, where the in-betweens are designed to bridge the gap of these two visualizations and explain the difference in a gradual manner. As opposed to a textual description, our morphing explains an unfamiliar visualization through purely visual means. We demonstrate our idea by ways of four visualization pair examples: data table … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 42 publications
0
45
0
Order By: Relevance
“…The main point of visualization is it should use minimal amount of resources to be effective and efficient [38][39]. Hence, good visualization techniques can highlight similarities and differences, show correlations and trends to provide the perceptivity in this process [39].…”
Section: Visualizationmentioning
confidence: 99%
“…The main point of visualization is it should use minimal amount of resources to be effective and efficient [38][39]. Hence, good visualization techniques can highlight similarities and differences, show correlations and trends to provide the perceptivity in this process [39].…”
Section: Visualizationmentioning
confidence: 99%
“…Creating a holistic view saves people from splitting their attention between multiple views. techniques they are comfortable using [44]. However, if they have complex data consisting of heterogeneous multi-dimensional attributes, representing it with simple, familiar visualizations may be challenging.…”
Section: Heda: the Benefitsmentioning
confidence: 99%
“…The visualization community recognizes this and is taking steps to improve visualization literacy within the general public. Recent efforts to improve visualization literacy investigate how instructional materials should be designed [18,20,36,37]. Ruchikachorn and Mueller demonstrated that by morphing visualizations from the familiar to the unfamiliar, participants could learn new representational forms [18].…”
Section: Visualization Literacymentioning
confidence: 99%
“…Recent efforts to improve visualization literacy investigate how instructional materials should be designed [18,20,36,37]. Ruchikachorn and Mueller demonstrated that by morphing visualizations from the familiar to the unfamiliar, participants could learn new representational forms [18]. Alper et al [37] have developed an online platform for children in grades K to 4 to learn about pictographs and bar charts.…”
Section: Visualization Literacymentioning
confidence: 99%